The Camparison of Harmonic Distortion Self-Excited Induction Generator with Isolated Synchronous Generator under Non-linear Loads - Refdinal Nazir; Krismadinata Krismadinata; Rizka Amalia (International Journal of Power Electronics and Drive Systems (IJPEDS), 2015)
In this paper, the harmonic distortion for Self-Excited Induction Generator (SEIG) and an isolated synchronous generator (ISG) under non-linear load during steady state conditions are analyzed. The voltage and current harmonics distortion for both generators are calculated using the transfer function method in frequency domain for SEIG and phasor diagram method for ISG. This analysis is done independently one by one component for all harmonic components appear. The analysis results for both generators are verified to the laboratory test results. For loading with the same non-linear load to both generators, the harmonics distortion on the stator windings of SEIG was smaller than compare ISG. In addition, the harmonic distortion effects on other loads connected to PCC point of SEIG was lower than the other loads connected to ISG.